Sustainable corporate entrepreneurship initiatives: a risk and reward analysis - Urban, Boris; Nikolov, Kristo (Technological and Economic Development of Economy, 2014)
Earlier studies recognize the importance of corporate entrepreneurship towards achieving a sustainable competitive advantage. This study proposes that the likelihood of individual participation in corporate entrepreneurship initiatives is contingent upon individual perceptions of rewards and risks. The research presents different scenarios, and tests several attributes that influence the decision to participate. Conjoint analysis utilisation simulates a real life situation where scenario analyses in varying combinations in terms of their intensity levels take place. The results indicate the most important attribute influencing the decision to participate is the probability of venture success followed closely by financial reward. As expected, job risk, pay risk and required effort are deterrents to participation; and individuals with past entrepreneurial experience are less concerned about job risk and have a higher positive perception regarding the probability of corporate venture success.